1972
DOI: 10.1128/iai.6.6.918-927.1972
|View full text |Cite
|
Sign up to set email alerts
|

Role of the K88 Antigen in the Pathogenesis of Neonatal Diarrhea Caused by Escherichia coli in Piglets

Abstract: The role of the K88 antigen of Escherichia coli in neonatal diarrhea of piglets was studied by comparing a K88-positive strain with three K88-negative strains derived from the K88-positive strain. K88 antigen was produced by the K88-positive strain in the intestinal tract of gnotobiotic piglets, whereas K88-negative strains did not regain the ability to synthesize K88 antigen. Synthesis of the antigen conferred different colonization characteristics on the four strains; K88-positive bacteria adhered to the muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
176
1
2

Year Published

1974
1974
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(183 citation statements)
references
References 37 publications
2
176
1
2
Order By: Relevance
“…Antigenic variants referred to as K88ab, -ac, and -ad ¢mbriae have been identi¢ed [2,3]. These ¢mbriae mediate the adhesion of E. coli K88 strains to the epithelial mucosa lining of the intestine [4] and thereby contribute to their virulence [5]. Inhibition of adhesion of E. coli K88 to the host at this stage may reduce the virulence of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Antigenic variants referred to as K88ab, -ac, and -ad ¢mbriae have been identi¢ed [2,3]. These ¢mbriae mediate the adhesion of E. coli K88 strains to the epithelial mucosa lining of the intestine [4] and thereby contribute to their virulence [5]. Inhibition of adhesion of E. coli K88 to the host at this stage may reduce the virulence of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli strains can elaborate tip-localized proteins on pap fimbria¢, which are important in uroepithelial attachment [39]. K88 and K99 are other E. Table 1 coli fimbrial antigens which complex with receptors on intestinal epithelium [40,41]. Oral microorganisms also possess a wide variety, of specific adhesin molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The K88 antigen was first described in 1961 as a serologically distinct antigen associated with E. coli strains isolated from pigs with edema disease and neonatal enteritis (105). It was later demonstrated that the K88 antigen was an adherence factor which facilitated colonization of the small intestine (6,65,158). This was confirmed by several in vivo and in vitro studies wherein adherence of K88-positive EPEC to intestinal villous epithelium was blocked by antisera against the K88 antigen (65,134,138,158).…”
Section: / Pili Of Enteropathogenic Escherichia Colimentioning
confidence: 92%
“…It was later demonstrated that the K88 antigen was an adherence factor which facilitated colonization of the small intestine (6,65,158). This was confirmed by several in vivo and in vitro studies wherein adherence of K88-positive EPEC to intestinal villous epithelium was blocked by antisera against the K88 antigen (65,134,138,158). Based on these findings, vaccine trials were carried out and demonstrated that sows vaccinated with K88-positive EPEC would produce high levels of colostral K88-specific antibody which would passively protect newborn suckling pigs from enteric disease produced by K88-positive EPEC (119,120).…”
Section: / Pili Of Enteropathogenic Escherichia Colimentioning
confidence: 99%